Impact of Biologically Active Complexes of L. rhamnosus GG and S. boulardii After Storage Under Low Temperatures on Biofilm Forming Ability in Corynebacteria - Isayenko, Olena; Knysh, Oksana; Popov, Mykola; Minukhin, Valeriy; Babych, Eugeny; Peretyatko, Olena (Problems of Cryobiology and Cryomedicine, 2021)
This paper describes the temperature regimens and shelf life of biologically active complexes (structural components and metabolites) of Lactobacillus rhamnosus GG and Saccharomyces boulardii, which have antimicrobial activity and reduce biofi lm formation in pathogenic agents of Corynebacterium spp. Preservation of biological activity of complexes after 6-month storage (observation period) at (−23 ± 1)°C and for 60 days (observation period) under hypothermia at (4 ± 1)°C has been demonstrated. The degree of inhibition of biofi lm formation in pathogenic corynebacteria depended on sensitivity of the Corynebacterium spp. test-culture strain to products of microbial origin. A mixture of lactobacillus and saccharomycete metabolites displayed weak biofi lm formation by toxicogenic strains of corynebacteria (p < 0.05). Our fi ndings testifi ed to a possible use of biologically active substances, stored at 4 and −23°C in designing the L. rhamnosus GG and S. boulardii complexes and in technological processes of their production to prevent the persistence of the diphtheria pathogens. Probl Cryobiol Cryomed 2021; 31(2): 127–138